Socio-Demographic Factors Are Related to Family Preparedness in Facing Disasters - widya Addiarto; Achmad Kusyairi (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
Disasters such as floods, earthquakes, and pandemics have been shown to affect the quality of life, mental health, and economic sustainability of affected communities. In response to these disasters, individuals are expected to prepare themselves and their families for the worst risks that can occur at any time. Currently, family preparedness is very important to be grown in social life. The purpose of this research is to describe the relationship between socio-demographic factors associated with family preparedness in urban disaster-prone areas in Probolinggo District. The research design used was descriptive analytic research design with a cross-sectional approach. The sample was selected using purposive sampling technique with a sample of 122 respondents. Furthermore, respondents will be given a questionnaire to determine or identify family preparedness variables. After that, the data was collected and processed with the help of SPSS 23 for windows using bivariate tests on each variable to determine its relationship with family preparedness. From the results of the bivariate test using Spearman rank, there is a significant relationship between socio-demographic factors and family preparedness including: gender (p=0.000), education (p=0.000), occupation (p=0.000), and knowledge with (p=0.015). Meanwhile, the variables of age (p=0.808) and social support (p=0.195) have no correlation with family preparedness (p value 0.05). These results indicate that it is important to improve family preparedness by correcting deficiencies in several factors that do not have a significant relationship from the research results